2010
DOI: 10.1007/s12519-011-0250-3
|View full text |Cite
|
Sign up to set email alerts
|

Childhood craniopharyngioma in Macedonia: incidence and outcome after subtotal resection and cranial irradiation

Abstract: the overall incidence of craniopharyngioma in the period of 1989-2008 in Macedonia was 1.43 per 1 000 000 person-years. Subtotal resection and systematic irradiation showed good life quality of survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It was perceived that after surgical treatment of craniopharyngioma there was a quick improvement of VA in the first 10 to 14 days, followed by a slower recovery during the period of several months or even years [4,[14][15][16]. Our data show that there was a statistically significant improvement of VA in 36% of patients and 28% of eyes, in the first 10 days after surgery.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It was perceived that after surgical treatment of craniopharyngioma there was a quick improvement of VA in the first 10 to 14 days, followed by a slower recovery during the period of several months or even years [4,[14][15][16]. Our data show that there was a statistically significant improvement of VA in 36% of patients and 28% of eyes, in the first 10 days after surgery.…”
Section: Discussionmentioning
confidence: 51%
“…The majority of authors agree that monocular or binocular loss of vision is a prevalent finding in young and adult craniopharyngioma patients [4,7,9,11,[13][14][15][16]. Van Effenterre and Boch [4] have found it in 80% of cases, while other studies have shown it to be in the range from 42% to 72% [7,11,13,15].…”
Section: Discussionmentioning
confidence: 98%
“…; Gucev et al. ; Lee & Hwang ). Postoperative visual disturbances continue to be a factor affecting the patient's quality of life (Prieto et al.…”
Section: Introductionmentioning
confidence: 99%
“…Craniopharyngioma contributes to 2-5% of all intracranial tumours in the whole population [2] and 5.6-14.1% among children [3][4][5][6]. Incidence rate is assessed in the whole population as 0.5-2/mln/year, on the average 1.3/mln/year [7][8][9][10]. In children, craniopharyngioma is one of the most frequent benign tumours of the central nervous system (CNS) and contributes to approx.…”
Section: Introductionmentioning
confidence: 99%
“…In children, craniopharyngioma is one of the most frequent benign tumours of the central nervous system (CNS) and contributes to approx. 56% of all cases of tumours of the sellar and suprasellar regions [9,10].…”
Section: Introductionmentioning
confidence: 99%